Preparation method of oxygen coordination nickel monatomic catalyst and application of oxygen coordination nickel monatomic catalyst in catalytic production of peroxide

By forming an oxygen-coordinated nickel single-atom catalyst with Ni-O4 structure on the oxidized carbon black support, the problem of low H2O2 synthesis efficiency in electrocatalytic 2e-ORR is solved, and a catalytic effect with high activity and high selectivity is achieved. It is suitable for Electrocatalyzed di-electron oxygen reduction reaction.

CN119221021APending Publication Date: 2024-12-31CENT SOUTH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411336871.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

In the prior art, electrocatalyzed 2e-ORR is often accompanied by 4e-ORR, resulting in a decrease in the synthesis efficiency and yield of H2O2, and it is necessary to develop highly selective and active electrocatalysts.

Method used

Oxidation carbon black is used as a support to form an oxygen-coordinated nickel single-atom catalyst with Ni-O4 structure through tert-butylphenol and nickel ions, and regulate the coordination structure of nickel atoms to improve the activity and selectivity of the di-electron oxygen reduction reaction.

Benefits of technology

It realizes a catalyst that efficiently generates H2O2 under electrocatalytic conditions, improves the activity of the catalyst and the selectivity of hydrogen peroxide, and is simple to operate and green and safe.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119221021A_ABST
    Figure CN119221021A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of an oxygen-coordinated nickel monatomic catalyst and application of the catalyst in catalytic production of peroxide.The preparation method comprises the steps that carbon black is calcined in a muffle furnace, cooled and ground, and oxidized carbon black is obtained; and dispersing the oxidized carbon black, tert-butylphenol and water-soluble nickel salt in a solvent, stirring until the mixture is dried, and performing heat treatment in an inert atmosphere to obtain the oxygen-coordinated nickel monatomic catalyst. Compared with nickel monatomic catalysts with other coordination structures, the Ni-O4 coordinated nickel monatomic catalyst has a more optimized electronic structure in 2e-ORR, so that the adsorption strength of an oxygen-containing intermediate is adjusted, and finally excellent catalytic activity and hydrogen peroxide selectivity are presented. The method has the advantages of simple synthesis steps, no need of over-high temperature treatment, low cost and extremely strong universality. The preparation method of the oxygen-coordinated nickel monatomic catalyst is expected to be expanded to other transition metal monatomic catalysts with different coordination structures.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of transition metal single-atom catalysts, and in particular to an oxygen-coordinated nickel single-atom catalyst and a preparation method thereof. Background Art

[0002] As an environmentally friendly oxidant, H2O2 has shown potential for application in many fields such as medicine, chemical industry, textiles and wastewater treatment, and the market demand continues to grow. - ORR synthesis of H2O2 is a mild, green and sustainable method that helps to achieve on-site production of H2O2, which is safe and convenient. However, the process is often accompanied by 4e - The occurrence of ORR seriously reduces the synthesis efficiency and yield of H2O2.

[0003] In view of the above problems, it is necessary to develop - ORR has highly selective and active electrocatalysts. The active sites of single-atom catalysts exist in the form of highly dispersed single atoms, which greatly improves the utilization rate of atoms. In traditional catalysts, the active sites are mostly in the form of clusters or particles, which are prone to bridge adsorption of oxygen molecules, which is not conducive to 2e - ORR. By regulating the type, coordination structure, and local microenvironment of the metal active center of the single-atom catalyst, electronic and geometric effects can be induced to promote 2e - ORR, inhibition 4e - ORR, thereby improving the yield and selectivity of H2O2. This provides a broad space for designing highly active and highly selective electrocatalytic oxygen reduction two-electron hydrogen peroxide catalysts.

[0004] Current research is used for 2e - The nickel single-atom catalysts for ORR are basically Ni-N4 or Ni-N x C y Although C and N atoms coordinate with Ni atoms to form a 2e - The structure has ORR activity, but the electronegativity of C and N atoms is weaker than that of O atoms. The strong electronegativity of O atoms attracts the electron cloud around Ni atoms, which helps stabilize the intermediate *OOH and inhibits its further reduction to H2O, thus facilitating the generation of H2O2. Although the strong electronegativity of O atoms helps the activity of Ni atomic sites and regulates the reaction path, the structure with higher Ni atom coordination formed by too many O atoms may also cause the electron orbit of Ni atoms to be over-occupied, thereby reducing its catalytic activity. Therefore, in catalyst design, it is necessary to find a balance between the number of O atoms coordinated by nickel and the catalytic activity. Summary of the invention

[0005] The technical problem to be solved by the present invention is to precisely control the coordination structure of metal single atoms and improve the 2e - ORR activity and hydrogen peroxide selectivity.

[0006] The technical solution adopted by the present invention to solve the technical problem is as follows:

[0007] A method for preparing an oxygen-coordinated nickel single-atom catalyst comprises the following steps:

[0008] Providing oxidized carbon black, water-soluble nickel salts, and tert-butylphenol;

[0009] The oxidized carbon black, the water-soluble nickel salt and the tert-butylphenol are dissolved in a solvent, mixed and dried to obtain a precursor; wherein the ratio of the oxidized carbon black, the water-soluble nickel salt and the tert-butylphenol is 50 mg: 0.001 mmol to 0.01 mmol: 0.05 mmol to 0.2 mmol;

[0010] The precursor is heat-treated in an inert atmosphere to obtain an oxygen-coordinated nickel single-atom catalyst; wherein the heat treatment temperature is 170°C to 230°C.

[0011] The nickel atoms in the oxygen-coordinated nickel single-atom catalyst exist in an atomically dispersed form, wherein there is no direct bonding between Ni atoms and Ni atoms. A Ni-O4 structure exists in the oxygen-coordinated nickel single-atom catalyst, and Ni atoms and O atoms mainly exist in a Ni-O coordination form to form a Ni-O4 structure.

[0012] The present invention is to obtain an oxygen-coordinated nickel single-atom catalyst with high activity and high hydrogen peroxide selectivity. Oxidized carbon black (OCB) is used as a carrier, nickel metal active sites are introduced by a ligand-assisted method, tert-butylphenol is used as a ligand, and a water-soluble nickel salt is used as a nickel source. Oxidized carbon black (OCB) has a high specific surface area and high surface energy, which is conducive to the dispersion of reactive active sites. In order to prepare the oxygen-coordinated nickel single-atom catalyst, the present invention uses tert-butylphenol as an organic ligand, which is combined with metal nickel ions to form a nickel-tert-butylphenol complex. The water-soluble nickel salt is ionized into nickel ions and anions in a solution, and the tert-butylphenol contains a phenolic hydroxyl group and a tert-butyl group. During the stirring process, the tert-butylphenol molecules in the solution collide with the nickel ions. When the oxygen atom of the phenolic hydroxyl group is sufficiently close to the empty orbit of the nickel ion, the lone pair of electrons of the oxygen atom will enter the empty orbit of the nickel ion to form a Ni-O coordination bond. The tert-butyl group is a bulky substituent. Although the tert-butyl group does not directly participate in the coordination in this process, its presence increases the steric hindrance of the tert-butylphenol molecule. This steric hindrance helps to protect the hydroxyl part and prevent it from being subjected to unnecessary chemical reactions or physical interference before coordination with nickel ions. The porosity of the oxidized carbon black OCB carrier can increase its specific surface area, and the introduction of a large number of oxygen-containing functional groups such as carbonyl groups can increase the hydrophilicity and surface energy of the carbon carrier, which is beneficial to the adsorption of the complex. Among them, the carbonyl group is polar and can form hydrogen bonds with water molecules. When this functional group is introduced to the surface of the carbon carrier, it will give the carbon carrier a certain hydrophilicity. The enhancement of hydrophilicity makes it easier for the carbon carrier to interact with polar molecules in the aqueous solution (such as nickel ions and tert-butylphenol in the complex), which is beneficial to the adsorption of the complex on the surface of the carbon carrier. Therefore, the nickel-tert-butylphenol complex formed by metallic nickel and tert-butylphenol will be adsorbed on the oxidized carbon black support during the stirring process. During the high-temperature stirring process of nickel salt and tert-butylphenol, the lone pair of electrons formed by the breaking of the hydrogen-oxygen bond of the phenolic hydroxyl group is more easily captured by the empty orbit of the nickel ion, forming a kinetically favorable and thermodynamically stable coordination bond, which helps one nickel ion to combine with four phenolic hydroxyl groups of tert-butylphenol to form a complex. When heated in an inert atmosphere, the nickel-tert-butylphenol complex adsorbed on the oxidized carbon black OCB support begins to pyrolyze. In this process, as the temperature increases, the complex is pyrolyzed and connected to the oxidized carbon black support, and the carbon atoms in the support coordinate with oxygen atoms to form Ni-OC bonds. In this process, nickel ions are more inclined to form a planar four-coordinate structure (Ni-O4), the formation of which is due to its lower energy state and higher lattice energy. Since the Ni-O4 structure has a higher geometric symmetry, the electron cloud distribution is more uniform, reducing the repulsive force between electrons, so this structure is more stable in energy. Therefore, an oxygen-coordinated nickel single atom catalyst is obtained.

[0013] The ratio of metal nickel ions to tert-butylphenol affects the ORR catalytic performance of oxygen-coordinated nickel single-atom catalysts. When the ratio of metal nickel ions to tert-butylphenol increases, it cannot provide enough ligands to stabilize Ni. 2+ , multiple Ni 2+ The ions may approach each other and form aggregates or clusters through the bridges of solvent molecules. The Ni 2+ The interaction between ions may change their electronic structure and catalytic active sites, resulting in a decrease in catalyst performance. Secondly, insufficient amounts of tert-butylphenol cannot provide enough oxygen atoms to coordinate with nickel atoms, and the complex will form Ni-C on the carbon support after thermal decomposition. x O y Coordination structure. The electronegativity of carbon atoms is weaker, and their ability to attract electrons to nickel atoms is not as good as that of oxygen atoms. Therefore, the adsorption energy of intermediates at this active site is higher, which is not conducive to 2e - ORR. When the ratio of metal nickel ions to tert-butylphenol decreases, the excess tert-butylphenol will occupy too many coordination positions, forming a higher coordination Ni-O structure. The electronic structure of this high-coordination Ni atom is not flexible enough due to its high coordination number, which is not conducive to the flow of electrons during the reaction. 2+ The nickel single atom catalyst with Ni-O4 structure has a higher 2e - ORR catalytic performance.

[0014] The temperature of the heat treatment of the precursor will affect the ORR catalytic performance of the oxygen-coordinated nickel single atom catalyst. The higher the temperature of the heat treatment of the precursor, the more violent the pyrolysis and rearrangement reactions the nickel-tert-butylphenol precursor may undergo. As the temperature increases, the O atoms obtain higher thermal energy, and the amplitude and frequency of their lattice vibrations gradually increase, making the lattice structure more unstable. When the lattice vibration reaches the critical point, some O atoms will obtain enough energy to overcome the constraints of the surrounding atoms, thereby breaking away from their original equilibrium position, breaking the Ni-O bond, and reducing the number of O atoms coordinated with the Ni atoms, thereby forming a Ni-O structure or Ni-C with a lower coordination number. x O y Coordination structure, the reaction activity is reduced. Due to the complete decomposition of organic ligands, Ni 2+It may be exposed, and a non-coordinated or lower-coordinated Ni site structure may be formed. When heat treated at low temperatures, the chemical bond between the nickel-tert-butylphenol precursor and the carrier cannot be fully formed, which will reduce its structural stability and may also cause the product to have a lower crystallinity. Low temperature will cause the Ni atoms to be unable to be fully dispersed on the carrier, making it easy for them to migrate or agglomerate during the reaction, and unable to form enough single-atom active sites. Tert-butylphenol may not be completely decomposed, causing it to remain on the surface, occupying active sites, hindering the contact between the reactants and the catalyst, thereby reducing the selectivity of hydrogen peroxide. Therefore, when the temperature of the heat treatment of the precursor is 170°C to 230°C, the ORR catalytic performance of the nickel single-atom catalyst is higher.

[0015] The oxygen-coordinated nickel single atoms obtained by the reaction are anchored on the OCB carrier. The small-sized nanoparticles have a larger specific surface area, which means that more catalytic active sites are exposed to the reaction environment, thereby increasing the contact opportunities between the catalyst and the reactants and accelerating the reaction rate. The nano-sized particles shorten the diffusion path of oxygen molecules on the catalyst surface and improve the mass transfer efficiency. In addition, the gaps between small nanoparticles also contribute to the rapid transmission of reactants and products. More importantly, the oxygen-coordinated nickel single atom structure Ni-O4 is more conducive to 2e than most Ni and other element coordination structures. - ORR. 2e - The ORR process mainly consists of the following steps: O2 is adsorbed on the active sites on the catalyst surface and reduced to *OOH through proton coupling and electron transfer. If the active sites have a moderate adsorption strength for *OOH, further proton coupling and electron transfer occur to generate *HOOH, and *HOOH desorbs from the surface to generate H2O2. If the adsorption strength of *OOH on the active sites is too high, it will be further reduced to generate H2O. If the adsorption strength of *OOH on the active sites is too low, it may not be able to stably exist on the catalyst surface. Compared with Ni-C coordination, Ni-O coordination is more conducive to 2e - In ORR, since the electronegativity of O atoms is higher than that of C atoms, O atoms can more effectively attract electrons from Ni atoms, resulting in a lower electron density of Ni atoms in the Ni-O coordination structure, which means that the coordination structure has a more moderate adsorption capacity for the intermediate *OOH, which can not only ensure the stable existence of *OOH on the catalyst surface, but also facilitate its desorption in subsequent steps. Therefore, it has a higher activity for the two-electron oxygen reduction reaction and is more conducive to improving the selectivity of hydrogen peroxide. In the Ni-O4 coordination structure, the Ni atom is completely surrounded by four O atoms, forming a relatively closed coordination environment. The compact and symmetrical spatial configuration helps to reduce the steric hindrance effect and make the reaction path smoother. At the same time, this configuration may also provide a stable adsorption site for *OOH, promote its directional adsorption and reaction, and facilitate the two-electron oxygen reduction reaction to produce H2O2.

[0016] Preferably, the ratio of the oxidized carbon black, the water-soluble nickel salt and the tert-butylphenol is 50 mg: 0.005 mmol: 0.075 mmol to 0.15 mmol. When the ratio of the oxidized carbon black, the water-soluble nickel salt and the tert-butylphenol is 50 mg: 0.005 mmol: 0.075 mmol to 0.15 mmol, the ORR catalytic performance of the nickel single atom catalyst is better.

[0017] Preferably, the tert-butylphenol is selected from at least one of p-tert-butylphenol, m-tert-butylphenol and o-tert-butylphenol. Preferably, the tert-butylphenol is p-tert-butylphenol.

[0018] Preferably, the ratio of the oxidized carbon black, the water-soluble nickel salt and the p-tert-butylphenol is 50 mg: 0.005 mmol: 0.1 mmol. The ratio of the oxidized carbon black, the water-soluble nickel salt and the p-tert-butylphenol is 50 mg: 0.005 mmol: 0.1 mmol, and the ORR catalytic performance of the nickel single atom catalyst is better.

[0019] Preferably, the heat treatment temperature is 190°C to 210°C, and the ORR catalytic performance of the nickel single atom catalyst is better. Preferably, the heat treatment temperature is 200°C.

[0020] Preferably, the water-soluble nickel salt is selected from at least one of nickel chloride, nickel nitrate, nickel acetate and nickel sulfate. Preferably, the water-soluble nickel salt is nickel chloride or nickel nitrate.

[0021] Preferably, the oxidized carbon black is prepared by the following steps:

[0022] The carbon black is calcined in air, cooled, and ground to obtain oxidized carbon black; wherein the calcination temperature is 500-650°C.

[0023] In order to obtain an oxygen-coordinated nickel single-atom catalyst with high activity and high hydrogen peroxide selectivity, the present invention first prepares oxidized carbon black OCB. For example, XC 72 carbon black is placed in a muffle furnace for calcination, and the air atmosphere of the muffle furnace causes the XC 72 carbon black to be oxidized in the muffle furnace. A sufficient calcination time is set to introduce a sufficient amount of oxygen functional groups. The calcination temperature is 500-650° C., and oxidized carbon black OCB can be formed.

[0024] Preferably, during the calcination of carbon black, the heating rate is 2 to 8 °C min -1 The holding time is 1 to 4 hours. During the heating process, a large number of oxygen-containing functional groups are generated on the carbon black.

[0025] Preferably, the oxidized carbon black, the water-soluble nickel salt and the tert-butylphenol are dissolved in a solvent, mixed and dried to obtain a precursor, comprising:

[0026] dissolving the oxidized carbon black in a volatile solvent to obtain an oxidized carbon black solution;

[0027] dissolving the water-soluble nickel salt in a volatile solvent to obtain a nickel salt solution;

[0028] dissolving the tert-butylphenol in a volatile solvent to obtain a tert-butylphenol solution;

[0029] The nickel salt solution and the tert-butylphenol solution are uniformly mixed, and then poured into the oxidized carbon black solution to obtain a mixed solution;

[0030] The mixed solution is heated and stirred, and then dried to obtain a precursor.

[0031] Specifically, oxidized carbon black, water-soluble nickel salt, and tert-butylphenol are first dissolved in a volatile solvent, respectively, and then the nickel salt solution and the tert-butylphenol solution are mixed to form a nickel-tert-butylphenol complex. The nickel-tert-butylphenol complex is then mixed into the oxidized carbon black solution to form a mixed solution, and the nickel-tert-butylphenol complex is adsorbed on the oxidized carbon black or the nickel-tert-butylphenol complex forms a bond with the oxidized carbon black.

[0032] The nickel salt solution and the tert-butylphenol solution are placed in a volatile solvent, stirred at a preset temperature, and then mixed with the oxidized carbon black solution, and stirred at a preset temperature, and finally heated and stirred until dry. The dried precursor is placed in a porcelain boat and kept warm for a certain period of time under an inert atmosphere to obtain an oxygen-coordinated nickel single atom catalyst.

[0033] Preferably, the volatile solvent is selected from at least one of deionized water, methanol and ethanol. The use of a volatile solvent is conducive to rapid drying to obtain a precursor.

[0034] Preferably, the concentration of oxidized carbon black in the oxidized carbon black solution is 2.5 to 10 mg·mL -1 .

[0035] Preferably, the concentration of the water-soluble nickel salt in the nickel salt solution is 0.01 to 0.06 mmol·mL -1 , the volume is 16μL~1mL. The concentration of tert-butylphenol in the tert-butylphenol solution is 0.01~0.06mmol·mL -1 , the volume is 0.8~20mL.

[0036] Preferably, the volatile solvent is ethanol, and the amount of the volatile solvent to be added is 1 to 20 mL.

[0037] Preferably, the water-soluble nickel salt and tert-butylphenol C 10 H 14The molar ratio of the substance of NiO to tert-butylphenol C is 1:10-40, and the amount of organic ligand is sufficient to ensure that the metal Ni ion is fully coordinated with the organic ligand. 10 H 14 The molar ratio of O is 1:15~30.

[0038] Preferably, the heating and stirring temperature is 40-70° C., the heating and stirring time is 2-4 h, and then the temperature is raised to 75-90° C. and stirred until dry, and the stirring time is sufficient to achieve sufficient pre-coordination and mutual dispersion of the metal Ni ions.

[0039] Preferably, the inert atmosphere is N2 or Ar, and the heat treatment holding time is 1 to 3 hours, so that the Ni atoms are firmly anchored on the carbon support. Preferably, the heat treatment holding time is 2 hours.

[0040] An oxygen-coordinated nickel single-atom catalyst can be obtained by the above-mentioned preparation method, and the coordination of nickel atoms and oxygen atoms is achieved. The overall morphology of the oxygen-coordinated nickel single-atom catalyst is interconnected nanoparticles, and the size of the particles is 40 to 60 nm, for example, it can be about 50 nm. Metal nickel atoms exist on oxidized carbon black in an atomically dispersed form, and there is no direct bonding between nickel atoms, and nickel atoms are only coordinated with oxygen atoms. The atomic percentage of nickel metal atoms in the oxygen-coordinated nickel single-atom catalyst is 0.20 to 0.40%, and the atomic percentage of oxygen is 8.5% to 9.1%. The uniformly dispersed small nanoparticles have a large specific surface area, which is beneficial to increase active sites, and is also beneficial to the diffusion and mass transfer of reactants and products. Ni is well dispersed in oxidized carbon black, without obvious Ni nanoparticles or clusters, and Ni is well dispersed in oxidized carbon black, which improves the utilization rate of Ni atoms.

[0041] An application of the oxygen-coordinated nickel single-atom catalyst as described above in the production of peroxide. The prepared oxygen-coordinated nickel single-atom catalyst can be used for electrocatalytic two-electron oxygen reduction to produce hydrogen peroxide.

[0042] The beneficial effects of the present invention are as follows:

[0043] (1) The oxygen-coordinated nickel single-atom catalyst prepared by the present invention has achieved excellent performance in the electrocatalytic two-electron oxygen reduction to produce hydrogen peroxide. -1 Under KOH and saturated O2 atmosphere, it exhibits high oxygen reduction reaction (ORR) activity and selectivity to produce H2O2.

[0044] (2) The method of the present invention is simple to operate, does not require complicated equipment and instruments, is green, safe and pollution-free, and can be extended to a variety of transition metal single-atom catalysts and a variety of organic ligands. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 This is the SEM picture of Example 1 NiOC-1: 20-200°C of the present invention;

[0046] Figure 2 The XRD patterns of NiOC-1:20-200°C in Example 1 of the present invention and the OCB of the comparative example;

[0047] Figure 3 TEM photo (a), HRTEM photo (b) and EDS element mapping (c) of NiOC-1: 20-200°C in Example 1 of the present invention;

[0048] Figure 4 This is the full XPS spectrum of NiOC-1: 20-200°C in Example 1 of the present invention;

[0049] Figure 5 This is the Ni 2p spectrum of NiOC-1:20-200°C in Example 1 of the present invention;

[0050] Figure 6 This is the O1s spectrum of NiOC-1:20-200°C in Example 1 of the present invention;

[0051] Figure 7 This is the Ni element K-edge XANES spectrum of NiOC-1:20-200°C in Example 1 of the present invention;

[0052] Figure 8 This is the EXAFS spectrum of Ni element at 20-200° C. in Example 1 NiOC-1 of the present invention;

[0053] Fig. 9 This is the contact angle test result of NiOC-1:20-200°C in Example 1 of the present invention;

[0054] Fig.10 It is the contact angle test result of OCB of the comparative example of the present invention;

[0055] Fig.11 This is a KPFM photograph of NiOC-1: 20-200°C in Example 1 of the present invention;

[0056] Fig.12 is a KPFM photograph of the OCB of the comparative example of the present invention;

[0057] Fig.13 The Zeta potential results of NiOC-1:20-200°C in Example 1 of the present invention and the OCB of the comparative example;

[0058] Fig.14LSV curves of NiOC-1: 20-200°C of Example 1 of the present invention, OCB of the comparative example, NiOC-1: 10-200°C of Example 2, and NiOC-1: 40-200°C of Example 3 under 0.1M KOH;

[0059] Fig.15 The H2O2 selectivity of Example 1 NiOC-1: 20-200°C, the OCB of the comparative example, Example 2 NiOC-1: 10-200°C and Example 3 NiOC-1: 40-200°C of the present invention;

[0060] Fig.16 is the electron transfer number of Example 1 NiOC-1: 20-200°C of the present invention, the OCB of the comparative example, Example 2 NiOC-1: 10-200°C and Example 3 NiOC-1: 40-200°C;

[0061] Fig.17 The LSV curves of NiOC-1: 20-200°C in Example 1 of the present invention, OCB in the comparative example, and NiOC-1: 20-170°C in Example 4 under 0.1M KOH;

[0062] Fig.18 The H2O2 selectivity of Example 1 NiOC-1: 20-200°C, the OCB of the comparative example, and Example 4 NiOC-1: 20-170°C of the present invention;

[0063] Fig.19 is the electron transfer number of NiOC-1: 20-200°C in Example 1 of the present invention, OCB in the comparative example, and NiOC-1: 20-170°C in Example 4;

[0064] Fig. 20 is the Tafel slope of NiOC-1: 20-200°C in Example 1 of the present invention, OCB in the comparative example, and NiOC-1: 20-170°C in Example 4;

[0065] Fig.21 CV curves of NiOC-1:20-200°C at different scan rates in Example 1 of the present invention;

[0066] Fig. 22 CV curves of OCB at different scan rates for the comparative example of the present invention;

[0067] Fig.23 The active area C of OCB of Example 1 NiOC-1:20-200℃ and the comparative example dl ;

[0068] Fig.24 The FE of NiOC-1 in Example 1 of the present invention: 20-200°C in a flow cellH2O2 and H2O2 partial current density;

[0069] Fig.25 This is the H2O2 yield of NiOC-1:20-200°C in the flow cell of Example 1 of the present invention. DETAILED DESCRIPTION

[0070] Through a mixed pyrolysis strategy, oxidized carbon black, nickel nitrate and 2,5-pyridinecarboxylic acid were mixed and hydrothermally treated, and then calcined in an inert gas to obtain a Ni-N1O3-C-based Ni single-atom catalyst, which has higher hydrogen peroxide selectivity than the traditional Ni-N4 coordination structure. However, the coordinated atoms around the Ni atoms of this material cannot be precisely controlled during the pyrolysis process, and the controllability is poor (O,N Coordination-Mediated Nickel Single-Atom Catalysts for High Efficiency Generation of H2O2.ACS Appl. Mater. Interfaces 2023, 15, 33665.).

[0071] After the iron nitrate and H3BTC are mixed and dried to form FeBTC metal organic dry gel, it is calcined at high temperature in an inert atmosphere, and then mixed with potassium hydroxide and calcined at high temperature for the second time to obtain a single atom catalyst with Fe-O4 motif, which has excellent 2e - ORR performance. However, the synthesis method of this material is complicated and the calcination temperature is high (Fe-O4MotifActivatedGraphiticCarbonviaOxo-BridgeforHighlySelectiveH2O2Electrosynthesis.Angew.Chem.Int.Ed.2024,e202410123).

[0072] More importantly, the above work, or the existing work, is basically aimed at obtaining metal single atom sites, and lacks attention to the binding strength of the metal atom coordination structure. In fact, when Ni atoms in single atom catalysts coordinate with atoms of different electronegativity, their electronic structure will change, which will affect the binding energy of the catalyst to the reaction intermediates, thereby affecting the selectivity of the reaction path. Reasonable single atom site coordination structure design helps to balance the adsorption strength of reaction intermediates and is beneficial to improving reaction selectivity.

[0073] The present invention will be further described below in conjunction with the embodiments and drawings.

[0074] Unless otherwise specified, the raw materials or chemical reagents used in the embodiments of the present invention are obtained through conventional commercial channels.

[0075] Oxidized carbon black catalyst comparative example

[0076] Oxidized carbon black (OCB) catalyst comparative example, the appearance is piled nanoparticles, the particle size is about 50nm. A large number of oxygen-containing functional groups are introduced into the sample.

[0077] Preparation method of comparative example of oxidized carbon black catalyst

[0078] Weigh 500 mg of untreated XC 72 carbon black into a porcelain boat and place it in a muffle furnace at 5 °C min -1 The temperature was raised to 550°C at a heating rate of 100 °C and kept at that temperature for 3 h. After naturally cooling to room temperature, the oxidized carbon black (OCB) was obtained by sufficient grinding.

[0079] As a comparison, the present invention prepares nickel-free single-atom oxidized carbon black OCB by the same method. XC 72 carbon black is placed in a muffle furnace for calcination, and the air atmosphere of the muffle furnace causes the XC 72 carbon black to oxidize in the muffle furnace. After testing, the appearance of the OCB of the comparative example of the present invention is interconnected nanoparticles, and the size of the particles is about 50nm. A large number of oxygen-containing functional groups are introduced into the sample.

[0080] Oxygen-coordinated nickel single atom catalyst Example 1

[0081] Oxygen-coordinated nickel single-atom catalyst (NiOC-1: 20-200°C) Example 1, the overall morphology is stacked nanoparticles, and the particle size is about 50nm. Metallic nickel atoms exist on oxidized carbon black in an atomically dispersed form, and there is no direct bonding between nickel atoms, and nickel atoms are only coordinated with oxygen atoms. The atomic percentage of nickel metal atoms in the oxygen-coordinated nickel single-atom catalyst is 0.32%, and the atomic percentage of oxygen is 8.95%.

[0082] Preparation method of oxygen-coordinated nickel single-atom catalyst embodiment 1

[0083] (1) Weigh 500 mg of untreated XC 72 carbon black into a porcelain boat and place it in a muffle furnace at 5 °C / min. -1 The temperature was raised to 550°C at a heating rate of 100 °C and kept at that temperature for 3 h. After naturally cooling to room temperature, the oxidized carbon black (OCB) was obtained by sufficient grinding.

[0084] (2) Disperse 50 mg of OCB in 10 mL of ethanol to obtain an OCB solution. Weigh 1 mmol of NiCl2 and dissolve it in 20 mL of deionized water to prepare 0.05 mmol mL -1 NiCl2 solution, accurately weigh 1mmol of p-tert-butylphenol and dissolve it in 20mL of deionized water to prepare 0.05mmol mL -14-tert-butylphenol solution. Accurately measure 100 μL NiCl2 solution and 2 mL 4-tert-butylphenol solution and mix them evenly. Then pour the mixed solution into the above OCB solution to obtain a mixed solution. Stir the mixed solution at 60°C for 2 hours, then increase the temperature to 80°C and continue stirring until dry. Place the dried precursor in a porcelain boat under N2 atmosphere at 5°C·min -1 The catalyst was heated to 200°C at a rate of 20°C and kept at this temperature for 2 hours. After cooling naturally to room temperature, the heat treatment was completed to obtain an oxygen-coordinated nickel single-atom catalyst (denoted as NiOC-1: 20-200°C).

[0085] For the convenience of comparison, step (1) of Example 1 is consistent with the comparative example of oxidized carbon black catalyst. Figure 1 As shown, the NiOC-1:20-200°C in Example 1 of the present invention presents a nanoparticle morphology, which has a high specific surface area and high surface energy, so that it can provide more active sites in the reaction, thereby enhancing the catalytic effect. Figure 2 As shown, in the XRD spectrum of NiOC-1:20-200°C in Example 1 of the present invention, there are only two peaks corresponding to amorphous carbon, and no diffraction peaks caused by nickel nanoparticles are found, indicating that the existence form of Ni on the oxidized carbon black is highly dispersed or amorphous. Figure 3 As shown in the HRTEM photo of NiOC-1:20-200°C in Example 1 of the present invention, the lattice of the material is found to be disordered, which is consistent with the XRD result. In addition, the element distribution in NiOC was measured using EDS elemental analysis technology, and it was found that Ni, O and C were uniformly distributed in the material. Figure 4 As shown, in the full XPS spectrum of NiOC-1:20-200°C in Example 1 of the present invention, characteristic peaks of Ni 2p, O 1s and C1s appear, indicating that only Ni, O and C elements exist, and no other elements exist. Figure 5 As shown in the XPS Ni 2p spectrum of NiOC-1:20-200°C in Example 1 of the present invention. Figure 6 As shown, the XPS C1s spectrum of NiOC-1:20-200°C in Example 1 of the present invention shows that the carbon atoms only exist in the coordination forms of CO and C=O. Figure 7 As shown, the XANES spectrum edge of NiOC-1:20-200℃ in Example 1 of the present invention has a higher binding energy than NiO and NiPc (i.e. nickel phthalocyanine), indicating that the Ni atoms in NiOC-1:20-200℃ are in an oxidized state due to the stronger electronegativity of O, which makes it have a higher positive charge density. The positively charged Ni atoms can attract O2 molecules, thereby improving the oxygen reduction ORR activity. Figure 8As shown, the FT-EXAFS of Example 1 NiOC-1:20-200°C of the present invention further reveals that the coordination environment of Ni is only Ni-O, and the coordination number is similar to that of nickel phthalocyanine, which is 4, and the corresponding bond length is The absence of Ni-Ni bonds further proves that Ni is atomically dispersed in Example 1 NiOC-1:20-200°C, and the coordination environment is Ni-O4. Fig. 9 As shown, the water contact angle of NiOC-1:20-200°C in Example 1 of the present invention is 62°. Fig.10 As shown, the water contact angle of the OCB of the comparative example of the present invention is 31°, proving that the hydrophobic ability of NiOC-1:20-200°C in Example 1 of the present invention is stronger than that of the OCB of the comparative example of the present invention. Hydrophobic surfaces usually have weaker hydrophilicity and smaller intermolecular interaction forces, which allows O2 molecules to enter and adsorb on the surface more easily. This property helps to increase the amount of O2 adsorbed on the surface of NiOC-1:20-200°C in Example 1, thereby increasing the initial rate of the ORR reaction. Appropriate hydrophobicity helps to weaken the adsorption of the intermediate *OOH by NiOC-1:20-200°C in Example 1 of the present invention, preventing it from being excessively reduced to H2O, thereby improving the selectivity of H2O2. As Fig.11 As shown, the KPFM of NiOC-1:20-200°C in Example 1 of the present invention shows that its average surface potential is 313 mV, which is Fig.12 The average surface potential of OCB of the comparative example of the present invention is shown in Figure 1. The average surface potential of NiOC-1:20-200°C is about 3 times that of OCB. The higher average surface potential can stabilize the intermediate *OOH adsorbed on the surface and inhibit its further reduction to H2O, thereby improving the selectivity of H2O2. Fig.13 As shown, compared with the OCB of the comparative example of the present invention, the NiOC-1:20-200°C of the present invention example 1 exhibits a more negative Zeta potential, indicating that its structure is more stable. Fig.17 As shown, the current density of the OCB of the comparative example of the present invention is lower than that of the embodiment 1 of the present invention. Fig.18 As shown, the hydrogen peroxide selectivity of the OCB of the comparative example of the present invention is much lower than that of Example 1 of the present invention.

[0086] like Fig.21 As shown, in the non-Faraday potential range of 0.05 to -0.05 V (vs. SCE), the voltages were 20, 40, 60, 80, and 100 mV·s -1 The CV curve of NiOC-1:20-200℃ was obtained by scanning rate. The C dl 9.82mF cm -2 .like Fig. 22As shown, in the non-Faraday potential range of 0.05 to -0.05 V (vs. SCE), the voltages were 20, 40, 60, 80, and 100 mV·s -1 The CV curve of OCB was obtained at a scan rate of Fig.23 As shown in the figure, the C of OCB is obtained by calculation and fitting. dl 4.65mF·cm -2 , NiOC-1: 20-200℃C dl It is almost twice that of OCB, which may be due to the fact that the introduction of Ni increases the number of active sites, thus enabling the material to have a larger electrochemically active surface area.

[0087] In order to further evaluate the gain effect of NiOC-1:20-200°C in Example 1 of the present invention, NiOC-1:20-200°C in Example 1 of the present invention was used as the working electrode, nickel foam was used as the counter electrode, and mercury / mercury oxide electrode was used as the reference electrode. -1 Assemble the flow cell with KOH as the electrolyte for testing. Fig.24 As shown, in Example 1 of the present invention, NiOC-1: 20-200°C, within the voltage range of 0.6 to 0.1V, FE H2O2 The partial current density of H2O2 is greater than 90% at 0.1V, and reaches 203mA·cm -2 .like Fig.25 The figure shows the yield of H2O2 at each potential of NiOC-1:20-200°C in Example 1 of the present invention. When the potential reaches 0.2V, the H2O2 yield reaches a maximum value of 2458.2mmol·L -1 ·h -1 .

[0088] The present invention prepares different samples by adjusting the ratio of metal nickel ions and organic ligands. The other steps are consistent with the above, only changing Ni 2+ By simply changing the ratio of metal ions and organic ligands in the feed, the coordination structure of the single atom catalyst can be changed.

[0089] Oxygen-coordinated nickel single atom catalyst Example 2

[0090] Oxygen-coordinated nickel single-atom catalyst (NiOC-1: 10-200°C) Example 2, the overall morphology is interconnected nanoparticles, and the particle size is about 50nm. Some metal nickel atoms exist on the oxidized carbon black in the form of clusters, and some nickel atoms exist on the oxidized carbon black in the form of atomic dispersion. The atomic percentage of nickel metal atoms in the nickel-supported oxidized carbon catalyst is 0.30%, and the atomic percentage of oxygen is 8.62%.

[0091] Preparation method of oxygen-coordinated nickel single-atom catalyst embodiment 2

[0092] The preparation method of Example 2 of oxygen-coordinated nickel single-atom catalyst (NiOC-1: 10-200°C) is similar to that of Example 1, except that in step (2), 2 mL of p-tert-butylphenol solution is adjusted to 1 mL of p-tert-butylphenol solution. Since the synthesis method and the carrier have not changed, the microscopic morphology of the obtained product is similar to that of Example 1. However, since the ratio of metal nickel ions to p-tert-butylphenol is changed, the coordination environment of the nickel atoms of the obtained product is different from that of Example 1, which ultimately leads to differences in catalytic performance.

[0093] After testing, the overall morphology of Example 2 NiOC-1: 10-200℃ of the present invention is interconnected nanoparticles, and the particle size is about 50nm. Some metal nickel atoms exist on the oxidized carbon black in the form of clusters, and some nickel atoms exist on the oxidized carbon black in the form of atomic-level dispersion. Fig.14 As shown, the current density of NiOC-1:10-200°C in Example 2 of the present invention is lower than that in Example 1 of the present invention. Fig.15 As shown, the hydrogen peroxide selectivity of NiOC-1:10-200°C in Example 2 of the present invention is lower than that in Example 1 of the present invention.

[0094] Oxygen-coordinated nickel single atom catalyst Example 3

[0095] Oxygen-coordinated nickel single-atom catalyst (NiOC-1: 40-200°C) Example 2, the overall morphology is interconnected nanoparticles, and the particle size is about 50nm. Metallic nickel atoms exist on the oxidized carbon black in an atomically dispersed form, and there is no direct bonding between nickel atoms, and nickel atoms are only coordinated with oxygen atoms. The atomic percentage of nickel metal atoms in the oxygen-coordinated nickel single-atom catalyst is 0.31%, and the atomic percentage of oxygen is 8.97%.

[0096] Preparation method of oxygen-coordinated nickel single-atom catalyst embodiment 3

[0097] The preparation method of Example 3 of oxygen-coordinated nickel single-atom catalyst (NiOC-1: 40-200°C) is similar to that of Example 1, except that in step (2), 2 mL of p-tert-butylphenol solution is adjusted to 4 mL of p-tert-butylphenol solution. Since the synthesis method and the carrier have not changed, the microscopic morphology of the obtained product is similar to that of Example 1. However, since the ratio of metal nickel ions to p-tert-butylphenol is changed, the coordination environment of the nickel atoms of the obtained product is different from that of Example 1, which ultimately leads to differences in catalytic performance.

[0098] After testing, the overall morphology of Example 3 NiOC-1: 40-200℃ of the present invention is interconnected nanoparticles, and the particle size is about 50nm. The metal nickel atoms exist on the oxidized carbon black in an atomically dispersed form, and there is no direct bonding between the nickel atoms. The nickel atoms are only coordinated with oxygen atoms, and a small amount of highly coordinated Ni-O6 may be formed, achieving a stable electronic configuration, which is not conducive to the flow of electrons during the reaction and reduces the reaction activity. Fig.14 As shown, the current density of NiOC-1:40-200°C in Example 3 of the present invention is lower than that in Example 1 of the present invention. Fig.15 As shown, the hydrogen peroxide selectivity of NiOC-1:40-200°C in Example 3 of the present invention is lower than that in Example 1 of the present invention.

[0099] The present invention prepares different samples by adjusting the pyrolysis temperature of the precursor. The other steps are consistent with the above, and only the heat treatment temperature in the inert atmosphere is changed. By simply changing the heat treatment temperature, the coordination structure of the nickel single atom catalyst can be changed.

[0100] Oxygen-Coordinated Nickel Single Atom Catalyst Example 4

[0101] Oxygen-coordinated nickel single-atom catalyst (NiOC-1: 20-170°C) Example 4, the overall morphology is interconnected nanoparticles, and the particle size is about 50nm. Metallic nickel atoms exist on the oxidized carbon black in an atomically dispersed form, and there is no direct bonding between nickel atoms, and nickel atoms are only coordinated with oxygen atoms. The atomic percentage of nickel metal atoms in the oxygen-coordinated nickel single-atom catalyst is 0.29%, and the atomic percentage of oxygen is 9.01%.

[0102] Preparation method of oxygen-coordinated nickel single-atom catalyst embodiment 4

[0103] The preparation method of Example 4 of oxygen-coordinated nickel single-atom catalyst (NiOC-1: 20-170°C) is similar to that of Example 1, except that in step (2), the heat treatment temperature of 200°C is adjusted to 170°C. Since the synthesis method, material ratio and carrier have not changed, the microscopic morphology of the obtained product is similar to that of Example 1. However, due to the change in the pyrolysis temperature, the coordination environment of the nickel atoms of the obtained product is different from that of Example 1, which ultimately leads to differences in catalytic performance.

[0104] After testing, the overall morphology of Example 4 NiOC-1:20-170℃ of the present invention is interconnected nanoparticles, and the particle size is about 50nm. The metal nickel atoms exist on the oxidized carbon black in an atomically dispersed form, and there is no direct bonding between the nickel atoms. The nickel atoms are only coordinated with oxygen atoms, and a small amount of saturated coordinated Ni-O6 may be formed, achieving a stable electronic configuration, which is not conducive to the flow of electrons in the reaction process, and cannot adsorb intermediates, reducing the reaction activity. Fig.17 As shown, the current density of NiOC-1:20-170°C in Example 4 of the present invention is lower than that in Example 1 of the present invention. Fig.18 As shown, the hydrogen peroxide selectivity of NiOC-1:20-170°C in Example 4 of the present invention is lower than that in Example 1 of the present invention.

[0105] Oxygen-Coordinated Nickel Single Atom Catalyst Example 5

[0106] Oxygen-coordinated nickel single-atom catalyst (NiOC-1: 20-230°C) Example 5, the overall morphology is interconnected nanoparticles, and the particle size is about 50nm. Metallic nickel atoms exist on the oxidized carbon black in an atomically dispersed form, and there is no direct bonding between nickel atoms. Nickel atoms are coordinated with oxygen atoms and carbon atoms. The atomic percentage of nickel metal atoms in the oxygen-coordinated nickel single-atom catalyst is 0.34%, and the atomic percentage of oxygen is 8.63%.

[0107] Preparation method of oxygen-coordinated nickel single-atom catalyst embodiment 5

[0108] The preparation method of Example 5 of oxygen-coordinated nickel single-atom catalyst (NiOC-1: 20-230°C) is similar to that of Example 1, except that in step (2), the heat treatment temperature of 200°C is adjusted to 230°C. Since the synthesis method, material ratio and carrier have not changed, the microscopic morphology of the obtained product is similar to that of Example 1. However, due to the change in the pyrolysis temperature, the coordination environment of the nickel atoms of the obtained product is different from that of Example 1, which ultimately leads to differences in catalytic performance.

[0109] After testing, the overall morphology of Example 5NiOC-1:20-230℃ of the present invention is interconnected nanoparticles, and the particle size is about 50nm. The metal nickel atoms exist on the oxidized carbon black in the form of atomic-level dispersion, and there is no direct bond between the nickel atoms. The nickel atoms coordinate with oxygen atoms and carbon atoms, and a small amount of Ni-O x C y The coordination structure of Fig.17 As shown, the current density of NiOC-1:20-230°C in Example 5 of the present invention is lower than that in Example 1 of the present invention. Fig.18 As shown, the hydrogen peroxide selectivity of NiOC-1:20-230°C in Example 5 of the present invention is lower than that in Example 1 of the present invention.

[0110] In order to further evaluate the gain effect of NiOC-1:20-200℃ in Example 1 of the present invention, the performance test was carried out in a three-electrode rotating disk electrode device with the electrocatalytic 2e-ORR reaction as the target scenario. The electrolyte was 0.1 mol / L KOH. Before the test, O2 was introduced into the electrolyte for 30 min. During the test, a saturated O2 atmosphere was always maintained. The catalyst underwent an ORR reaction on the disk electrode surface of the rotating disk electrode. After 2e - The H2O2 generated by the pathway is collected and oxidized by the Pt ring portion of the rotating ring disk electrode. Based on the current calculation of LSV, the H2O2 selectivity and the number of transferred electrons (n) of Example 1 NiOC-1: 20-200°C, the comparative example OCB, Example 2 NiOC-1: 10-200°C and Example 3 NiOC-1: 40-200°C of the present invention are obtained. Fig.15 As shown, the selectivity of NiOC-1:20-200℃ in Example 1 of the present invention to H2O2 is greater than 90% in the voltage range of 0.65-0.15V, and the selectivity reaches a maximum value of 91.7% at 0.32V, while the selectivity of H2O2 of the comparative example OCB, Example 2 NiOC-1:10-200℃ and Example 3 NiOC-1:40-200℃ are all below 90%. Fig.16 As shown, when NiOC-1:20-200℃ in Example 1 of the present invention is at 0.65-0.1V, the number of transferred electrons of NiOC-1:20-200℃ is around 2.2, indicating that the main pathway of the ORR reaction occurring at NiOC-1:20-200℃ is two electrons. The number of transferred electrons of the comparative example OCB, Example 2 NiOC-1:10-200℃ and Example 3 NiOC-1:40-200℃ are all above 2.5. The reason for the difference in performance may be that the change in the ratio of metal ions and organic ligands affects the change in the coordination environment of the metal Ni at the active site, resulting in different adsorption strengths of the intermediate *OOH, showing different 2e - ORR performance.

[0111] The H2O2 selectivity and the number of transferred electrons (n) of Example 1 NiOC-1: 20-200°C, the comparative example OCB, Example 4 NiOC-1: 20-170°C and Example 5 NiOC-1: 20-230°C of the present invention are calculated based on the LSV current. Fig.18 As shown, the H2O2 selectivity of the comparative example OCB, Example 4 NiOC-1: 20-170°C and Example 5 NiOC-1: 20-230°C are all below 80%. Fig.19As shown, the number of transferred electrons of the comparative example OCB, Example 4 NiOC-1: 20-170℃ and Example 5 NiOC-1: 20-230℃ are all above 2.5. The reason for the difference in performance may be that the change in temperature affects the change in the oxygen content in the material, resulting in a change in the coordination environment of the active site metal Ni, which leads to different adsorption strengths of the intermediate *OOH, showing different 2e - ORR performance. Fig. 20 As shown, the Tafel slopes of the comparative example OCB, Example 4 NiOC-1: 20-170°C and Example 5 NiOC-1: 20-230°C are 59.63, 90.05 and 61.22 mV·dec -1 The minimum Tafel slope of NiOC-1:20-200°C in Example 1 of the present invention is 55.19 mV·dec -1 , proving that it has faster reaction kinetics.

[0112] Oxygen-Coordinated Nickel Single Atom Catalyst Example 6

[0113] Oxygen-coordinated nickel single atom catalyst Example 6, the overall morphology is stacked nanoparticles, the particle size is about 50nm. Metal nickel atoms exist on the oxidized carbon black in an atomically dispersed form, and there is no direct bonding between nickel atoms, and the nickel atoms are only coordinated with oxygen atoms.

[0114] Preparation method of oxygen-coordinated nickel single-atom catalyst embodiment 6

[0115] (1) Weigh 500 mg of untreated XC 72 carbon black into a porcelain boat and place it in a muffle furnace at 2 °C / min. -1 The temperature was raised to 500°C at a heating rate of 100 °C and kept at that temperature for 1 h. After naturally cooling to room temperature, the oxidized carbon black was obtained by sufficient grinding.

[0116] (2) Disperse 50 mg of oxidized carbon black in 10 mL of ethanol to obtain an oxidized carbon black solution. Weigh 0.2 mmol of Ni(NO3)2 and dissolve it in 20 mL of deionized water to prepare 0.01 mmol mL -1 Ni(NO3)2 solution, accurately weigh 0.2mmol m-tert-butylphenol and dissolve it in 20mL of deionized water to prepare 0.01mmol mL -1 100 μL Ni(NO3)2 solution and 5 mL m-tert-butylphenol solution were accurately weighed and mixed evenly, and then the mixed solution was poured into the above oxidized carbon black solution to obtain a mixed solution. The mixed solution was fully stirred at 40°C for 2 h, and then the temperature was raised to 90°C and continued to stir until dry. The dried precursor was placed in a porcelain boat under Ar atmosphere at 3°C·min -1The mixture was heated to 200°C at a rate of 1.50°C and kept at this temperature for 2 hours. After cooling naturally to room temperature, the heat treatment was completed to obtain an oxygen-coordinated nickel single atom catalyst.

[0117] Oxygen-Coordinated Nickel Single Atom Catalyst Example 7

[0118] Oxygen-coordinated nickel single atom catalyst Example 7, the overall morphology is stacked nanoparticles, the particle size is about 50nm. Metal nickel atoms exist on the oxidized carbon black in an atomically dispersed form, and there is no direct bonding between nickel atoms, and the nickel atoms are only coordinated with oxygen atoms.

[0119] Preparation method of oxygen-coordinated nickel single-atom catalyst embodiment 7

[0120] (1) Weigh 500 mg of untreated XC 72 carbon black into a porcelain boat and place it in a muffle furnace at 2 °C / min. -1 The temperature was raised to 500°C at a heating rate of 100 °C and kept at that temperature for 1 h. After naturally cooling to room temperature, the oxidized carbon black was obtained by sufficient grinding.

[0121] (2) Disperse 50 mg of oxidized carbon black in 10 mL of ethanol to obtain an oxidized carbon black solution. Weigh 0.2 mmol of Ni(NO3)2 and dissolve it in 20 mL of deionized water to prepare 0.01 mmol mL -1 Ni(NO3)2 solution, accurately weigh 0.4mmol m-tert-butylphenol and dissolve it in 40mL of deionized water to prepare 0.01mmol mL -1 1 mL of Ni(NO3)2 solution and 20 mL of tert-butylphenol solution were accurately weighed and mixed evenly, and then the mixed solution was poured into the above-mentioned oxidized carbon black solution to obtain a mixed solution. The mixed solution was fully stirred at 40°C for 2 h, and then the temperature was raised to 90°C and continued to stir until dry. The dried precursor was placed in a porcelain boat under an Ar atmosphere at 3°C·min -1 The mixture was heated to 200°C at a rate of 1.50°C and kept at this temperature for 2 hours. After cooling naturally to room temperature, the heat treatment was completed to obtain an oxygen-coordinated nickel single atom catalyst.

[0122] Oxygen-Coordinated Nickel Single Atom Catalyst Example 8

[0123] Oxygen-coordinated nickel single-atom catalyst Example 8, the overall morphology is interconnected nanoparticles, the particle size is about 50nm. Metallic nickel atoms exist on the oxidized carbon black in an atomically dispersed form, and there is no direct bonding between nickel atoms, and nickel atoms are only coordinated with oxygen atoms.

[0124] Preparation method of oxygen-coordinated nickel single-atom catalyst embodiment 8

[0125] (1) Weigh 500 mg of untreated XC 72 carbon black into a porcelain boat and place it in a muffle furnace at 8 °C / min.-1 The temperature was raised to 650°C at a heating rate of 100 °C and kept at that temperature for 4 h. After naturally cooling to room temperature, the oxidized carbon black was obtained by sufficient grinding.

[0126] (2) Disperse 50 mg of oxidized carbon black in 10 mL of ethanol to obtain an OCB solution. Weigh 1.2 mmol of NiSO4 and dissolve it in 20 mL of deionized water to prepare 0.06 mmol mL -1 1.2 mmol of p-tert-butylphenol was accurately weighed and dissolved in 20 mL of deionized water to prepare 0.06 mmol mL -1 4-tert-butylphenol solution. Accurately measure 100 μL NiCl2 solution and 2 mL 4-tert-butylphenol solution and mix them evenly. Then pour the mixed solution into the above oxidized carbon black solution to obtain a mixed solution. Stir the mixed solution at 60°C for 2 hours, then increase the temperature to 80°C and continue stirring until dry. Place the dried precursor in a porcelain boat under N2 atmosphere at 5°C·min -1 The mixture was heated to 200°C at a rate of 1.50°C and kept at this temperature for 2 hours. After cooling naturally to room temperature, the heat treatment was completed to obtain an oxygen-coordinated nickel single atom catalyst.

Claims

1. A method for preparing an oxygen-coordinated nickel single-atom catalyst, characterized in that: Includes steps: Providing oxidized carbon black, water-soluble nickel salts, and tert-butylphenol; The oxidized carbon black, the water-soluble nickel salt and the tert-butylphenol are dissolved in a solvent, mixed and dried to obtain a precursor; wherein the ratio of the oxidized carbon black, the water-soluble nickel salt and the tert-butylphenol is 50 mg: 0.001 mmol to 0.01 mmol: 0.05 mmol to 0.2 mmol; The precursor is heat-treated in an inert atmosphere to obtain an oxygen-coordinated nickel single-atom catalyst; wherein the heat treatment temperature is 170°C to 230°C.

2. The method for preparing the oxygen-coordinated nickel single-atom catalyst according to claim 1, characterized in that: The ratio of the oxidized carbon black, the water-soluble nickel salt and the tert-butylphenol is 50 mg: 0.005 mmol: 0.075 mmol to 0.15 mmol; The temperature of the heat treatment is 190° C. to 210° C., and the heat preservation time of the heat treatment is 1 to 3 hours.

3. The method for preparing the oxygen-coordinated nickel single-atom catalyst according to claim 1, characterized in that: The tert-butylphenol is selected from at least one of p-tert-butylphenol, m-tert-butylphenol, and o-tert-butylphenol, and the water-soluble nickel salt is selected from at least one of nickel chloride, nickel nitrate, nickel acetate, and nickel sulfate; the oxygen-coordinated nickel single-atom catalyst has a Ni-O4 structure; the heat treatment temperature is 200°C, and the heat treatment holding time is 2h; the ratio of the oxidized carbon black, the water-soluble nickel salt, and the p-tert-butylphenol is 50mg:0.005mmol:0.1mmol.

4. The method for preparing the oxygen-coordinated nickel single-atom catalyst according to any one of claims 1 to 3, characterized in that: The oxidized carbon black is prepared by the following steps: The carbon black is calcined in air, cooled, and ground to obtain oxidized carbon black; wherein the calcination temperature is 500-650°C.

5. The method for preparing the oxygen-coordinated nickel single-atom catalyst according to claim 4, characterized in that: The heating rate of the calcination is 2 to 8 °C min -1 , the insulation time is 1 to 4 hours.

6. The method for preparing the oxygen-coordinated nickel single-atom catalyst according to any one of claims 1 to 3, characterized in that: The oxidized carbon black, the water-soluble nickel salt and the tert-butylphenol are dissolved in a solvent, mixed and dried to obtain a precursor, comprising: dissolving the oxidized carbon black in a volatile solvent to obtain an oxidized carbon black solution; dissolving the water-soluble nickel salt in a volatile solvent to obtain a nickel salt solution; dissolving the tert-butylphenol in a volatile solvent to obtain a tert-butylphenol solution; The nickel salt solution and the tert-butylphenol solution are uniformly mixed, and then poured into the oxidized carbon black solution to obtain a mixed solution; The mixed solution is heated and stirred, and then dried to obtain a precursor.

7. The method for preparing the oxygen-coordinated nickel single-atom catalyst according to claim 6, characterized in that: The volatile solvent is selected from at least one of deionized water, methanol and ethanol; The concentration of oxidized carbon black in the oxidized carbon black solution is 2.5 to 10 mg·mL -1 ; The concentration of the water-soluble nickel salt in the nickel salt solution is 0.01 to 0.06 mmol·mL -1 ; The concentration of tert-butylphenol in the tert-butylphenol solution is 0.01 to 0.06 mmol·mL -1 ; The heating and stirring temperature is 40-70°C, and the heating and stirring time is 2-4h; the drying temperature is 75-90°C.

8. An oxygen-coordinated nickel single-atom catalyst, characterized in that: The catalyst is prepared by the method for preparing the oxygen-coordinated nickel single-atom catalyst as described in any one of claims 1 to 7.

9. The oxygen-coordinated nickel single-atom catalyst according to claim 8, characterized in that: The particle size of the oxidized carbon black in the oxygen-coordinated nickel single-atom catalyst is 40-60 nm, the atomic percentage of nickel metal atoms is 0.2%-0.4%, and the atomic percentage of oxygen is 8.5%-9.1%.

10. Use of the oxygen-coordinated nickel single-atom catalyst as claimed in any one of claims 8 to 9 in producing peroxide.